BULKFILL TECHNIQUES WITH INTERMEDIATE LAYER TO MARGINAL ADAPTATION RESTORATION OF CLASS II COMPOSITE RESIN - Mochammad Raidjffan Zulkarnaen Tabona; Adioro Soetojo; Ira Widjiastuti (Conservative Dentistry Journal, 2021)
Background: Dental caries is a hard tissue disease caused by bacterial metabolic activity that causes demineralization, teeth that have caries should be filled in order to function again. One of the restorative materials closer to natural teeth is composite resin because it is the same colour as natural teeth and is easy to shape. As for the placement technique, bulkfill is also used because it is more time-efficient, and irradiation is accompanied by applying the restoration material in one batch. However, the bulkfill technique often causes micro-leakage of dental caries deposition. The intermediate layer is an intermediate layer used to prevent micro-leakage at the edges of the restoration as a base layer for restoration to create a good adaptation before applying packable composite resin. Therefore, bulkfill coating technique with the intermediate layer can reduce the risk of microleakage. Purpose: To describe the bulkfill technique with an intermediate layer against marginal adaptation with class II composite resin restorations. Review: The literature sources used in the preparation of the articles through several databases with descriptions. More journals say that micro-leakage in class II cavity deposition with the intermediate layer technique is better than the bulkfill technique because the intermediate layer technique has better bond strength than the bulkfill technique. If the Bulkfill technique is modified with the Intermediate layer technique, it can show good correlation and internal adaptation. Conclusion: Bulkfill technique with an intermediate layer against marginal adaptation with class II composite resin restorations can reduce the microleakage rate by reducing the polymerization's shrinkage strain.